A Carbohydrate-based Elastomer with Tunable Properties for Sensing Applications. (22nd January 2018) - Liu, Haoran; Ge, Jun; Lin, Xiao; Yang, Huilin; Yang, Lei
ABSTRACT: Flexible sensors are fundamental components of flexible electronics allowing a great number of applications from compliant robots to biomonitoring devices. The present work developed a carbohydrate-based elastomer (CBE) which possesses flexibility and tunable properties to meet the requirements of several sensing applications. Specifically, CBE was engineered to have high elasticity and sensing capabilities to humidity, stress and strain, enabling possible applications for monitoring physiological and external mechanical stimuli. These sensing capabilities of CBE were also adjustable to meet the requirements of applications such as electronic skin and wearable electronics.